Factors contributing to educational outcomes for First Nations students from remote communities: A systematic review - Guenther, John; Lowe, Kevin; Burgess, Catherine; Vass, Greg; Moodie, Nikki (The Australian Educational Researcher, 2019)
Education for Australian First Nations students living in remote communities has long been seen as an intractable problem. Ten years of concerted effort under Closing the Gap and related policy initiatives has done little to change outcomes beyond small, incremental improvements. Programmes and strategies promising much have come and gone, and most have died a quiet death. This apparent failure leaves the context of remote education ripe for the picking. If we can demonstrate what works and why, it may provide an answer to the problem. This systematic review aims to uncover what research reveals about what does make a difference to outcomes for students. The review found 45 papers that provide considerable evidence to show what is and is not effective. The review also found several issues that have little or no evidence and which could be the subject of more research. No Full Text